(untitled) (Research, Society and Development, 2022)
The purpose of this article is to present an analysis of the right to education and inclusion of people with disabilities and, in particular, remote teaching in Brazilian and Portuguese education in the context of the Covid 19 pandemic, for people with visual impairments (DV). This topic is of fundamental importance, since such students have the right to education guaranteed by law, both in Brazil and in Portugal. However, difficulties are encountered in accessing the formal educational process due to the historical character of exclusion of people with disabilities. The experiences lived by the authors refer to the main facilities and difficulties encountered by people with VI, the possibility and the need for mediation exercised by the teacher in the form of Distance Education (DE), as well as in remote teaching. In this sense, the issue of digital accessibility is highlighted, as a mechanism to reach any and all content on the web, in which people, regardless of their sensory difficulties or needs, must have autonomy and independence to participate in these environments. Thus, it will be initially presented, in a chronological way, legal frameworks of both countries that address social and school inclusion. Furthermore, considering the context of the Covid19 pandemic, remote teaching and its role for students with VI will be highlighted. The research approach is qualitative, bibliographic and documentary. The results indicate that the pandemic situation was complex and challenging, difficulties in addition to the new format, were experienced by people with VI were also present in the school scenario and that the need for teachers and students to reinvent themselves is undeniable.